Innovative approaches to blood-brain barrier modelling: The chip revolution - Avijit Bej; Nandita Mandal; Anwesha Das; Arijit Nandi (Next Nanotechnology)
The blood-brain barrier (BBB) is essentially involved in regulating the communication between the neurons in the central nervous system (CNS) and the rest of the body after excluding undesirable elements that may harm the neural tissues. The traditional in vivo models have some limitations in mimicking the sophisticated physiology and function of the BBB. As a result of these technical developments, researchers have been able to establish or design more controlled BBB platforms referred to as the BBB on a chip. These miniaturized models mimic structural and functional properties of the BBB and allow for monitoring of immediate integrity, permeability, and effects of drugs. This review aims to present the most recent advancement of BBB-on-a-chip technology by considering its design, fabrication method, and application in drug screening and disease modelling. It also discusses the difficulties in modelling the BBB, the comparison between various platforms, and the research direction that may help enhance these systems. Despite their limitations, BBB-on-a-chip platforms are a promising development for closing the disparity between the models and clinics and may help to improve the knowledge of neurovascular biology and the creation of new therapeutic interventions.